Faktor-Faktor Yang Mempengaruhi Perilaku Masyarakat Dalam Memelihara Ikan Cupang (Betta Splendens) Untuk Pemberantasan Sarang Nyamuk Demam Berdarah Dengue Di Kota Pontianak - Agustiansyah Agustiansyah; Harbandinah Pietojo; Ari Udiyono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2006)
Background: High humidity, high population density, rainy season and community habit in storing rain water in large water jar are estimated as the major factors in increasing DHF cases in Pontianak city. Raising cupang fish has become an alternative way to decrease the number of aedes agepty larva. Cupang fishes, besides they have many beautiful colors andforms, they have also recognized as masquito larva eater. Recently many people have been interesting in raising these fishes in Pontianak city.This study identifies the factors such as knowledge of cupang fish breeder and DHF disease, personal factors including profit of raising cupang fish and the number of family members influence the respondent behaviour in breeding cupang fish.Method : A proportional random sampling technique has been used to select 96 sample from four subdistricts in Pontianak city. The data was analysed by using univariate, bivariate and multivariate techniques.Results : The profit of money , the number of family members, knowledge of respondent in terms of DHF disease and cupang fish breeder have significant relationships to the practice of cupang fish breeder. Logistic regression shows that knowledge of DHF disease and cupangfish breeder, and the number of family members are the predictor variables which influence the practice of respondents in raising cupang fish.Keyword : Community behaviour, Cupang fish breeder, DHF